DINAMIKA INTERAKSI SOSIAL DAN PERUBAHAN NILAI BUDAYA PADA GENERASI Z DI KOTA SERANG DALAM ERA DIGITALISASI - Maulana, Reza; Safira Tri Aprilia; Ratu Siti Nurhasanah; Melani; Desiska; Friska Maudina Zamri; Nazwa Zahra Tirtana; Yesi Oktaviana; Listiana Nova; Lilis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digitalization has significantly transformed the patterns of social interaction and cultural values of Generation Z (Gen Z) in Banten Province. This study aims to analyze the frequency of social media use among adolescents, its influence on local cultural values, and the changes in real-world social interaction patterns. Using a qualitative approach through structured interviews and field observations, primary data were collected from various sources, including students, youth community leaders, and local adolescents in Banten, particularly in Pandeglang Regency and Kasemen District. The findings reveal that although digital technology provides remarkable convenience in communication, learning, and organizational management, it also presents significant challenges. These challenges include shifts in social ethics influenced by the culture of Fear of Missing Out (FOMO), social alienation in real life, and reduced participation in regional traditions. However, the study also identifies a balanced adaptation pattern, where Gen Z is aware of the negative impacts of digital devices while remaining optimistic about utilizing digital platforms for educational purposes and the promotion of local culture. This research concludes that strengthening digital literacy grounded in local wisdom is essential to preserve identity and maintain noble cultural values in the modern era.